Sustainable Financial Implementation In Supporting The National Economic Recovery Program In The Covid-19 Pandemic. Study On MSME Production Sector In Tolitoli Regency, Central Sulawesi : Indonesia - Edi Yanto; Rendy Aziz Syaputra (Institute of Computer Science (IOCS), 2022)
This research was conducted using a field research method that aims to determine the implementation of sustainable finance in supporting the national economic recovery program during the COVID-19 pandemic, focusing research on the environmentally friendly MSME production sector in Tolitoli Regency, Central Sulawesi. Through descriptive data analysis with a phenomenological approach, it is found that the implementation of sustainable finance in Tolitoli has been going quite well based on several sources of information. From Himbara banking financial services institutions (BRI, Mandiri and BNI), the average funding disbursed per business unit is IDR 50,000,000 to IDR 100,000,000 / business unit or in the range of less than IDR 200,000,000. -/business unit. The economic condition in Tolitoli also looks quite good through the trend of increasing aspects of employment and per capita income, then the sustainability of sustainable business sectors such as the agricultural sector. In addition, the better financial performance of the MSME production sector during the Covid-19 pandemic has an impact on accelerating the achievement of economic recovery in the regions and automatically contributing to national economic recovery. Of the 31 MSME units recorded, the average ROA and NPM values ​​were 187.57% and 63.24%, respectively, indicating good conditions for the survival of a business, especially micro, small and medium scale. This result certainly indicates a fairly good indicator for economic conditions in the Tolitoli Regency area during the Covid-19 pandemic until the new normal era takes place.